Phase 1 Human Immunodeficiency Virus (HIV) Vaccine Trial to Evaluate the Safety and Immunogenicity of HIV Subtype C DNA and MF59-Adjuvanted Subtype C Envelope Protein. (4th January 2020) - Hosseinipour, Mina C; Innes, Craig; Naidoo, Sarita; Mann, Philipp; Hutter, Julia; Ramjee, Gita; Sebe, Modulakgotla; Maganga, Lucas; Herce, Michael E; deCamp, Allan C; Marshall, Kyle; Dintwe, One; et al.
Abstract: Background: The Pox-Protein Public-Private Partnership is performing a suite of trials to evaluate the bivalent subtype C envelope protein (TV1.C and 1086.C glycoprotein 120) vaccine in the context of different adjuvants and priming agents for human immunodeficiency virus (HIV) type 1 (HIV-1) prevention. Methods: In the HIV Vaccine Trials Network 111 trial, we compared the safety and immunogenicity of DNA prime followed by DNA/protein boost with DNA/protein coadministration injected intramuscularly via either needle/syringe or a needle-free injection device (Biojector). One hundred thirty-two healthy, HIV-1–uninfected adults were enrolled from Zambia, South Africa, and Tanzania and were randomized to 1 of 6 arms: DNA prime, protein boost by needle/syringe; DNA and protein coadministration by needle/syringe; placebo by needle/syringe; DNA prime, protein boost with DNA given by Biojector; DNA and protein coadministration with DNA given by Biojector; and placebo by Biojector. Results: All vaccinations were safe and well tolerated. DNA and protein coadministration was associated with increased HIV-1 V1/V2 antibody response rate, a known correlate of decreased HIV-1 infection risk. DNA administration by Biojector elicited significantly higher CD4 + T-cell response rates to HIV envelope protein than administration by needle/syringe in the prime/boost regimen (85.7% vs 55.6%; P = .02), but not in the coadministration regimen (43.3% vs 48.3%; P = .61). Conclusions: Both the prime/boost and coadministration regimens are safe and may be promising for advancement into efficacy trials depending on whether cellular or humoral responses are desired. Clinical Trials Registration: South African National Clinical Trials Registry (application 3947; Department of Health [DoH] no. DOH-27–0715–4917) and ClinicalTrials.gov (NCT02997969). Abstract : DNA and protein coadministration was associated with increased human immunodeficiency virus (HIV) type 1 V1/V2 antibody response. Biojector DNA administration elicited significantly greater CD4 + T-cell responses to HIV envelope protein than needle/syringe in the prime/boost but not the coadministration regimen.